Effect of dietary incorporation of Chlorella vulgaris and CAZyme supplementation on the hepatic proteome of finishing pigs - Ribeiro, David M. (2022)
The combination of several factors, including an increase in world population and living standards in developing countries and world dependency on conventional crop imports drive a search for alternative feedstuffs for poultry and pig diets. This would reduce the environmental impact associated with the foreseeable increase in the demand for animal products. One of such alternatives are microalgae, a diverse group of aquatic organisms with interesting nutritional properties. Chlorella vulgaris is a green microalga with a crude protein content comparable to that of soybean meal. However, its recalcitrant cell wall prevents it from being used as a nutrient source in monogastric diets. CAZyme supplementation is a putative strategy to increase its nutritional value, aiming at disrupting the cell wall and make intracellular nutrients available for digestion. The impact of these dietary strategies on the hepatic metabolism is currently unknown. The objective of this study was to evaluate the hepatic proteome of pigs fed with 5% C. vulgaris with or without CAZyme supplementation. Microalga inclusion has affected lipid metabolism and oxidative stress. CAZyme supplementation has caused higher oxidative stress in the liver, possibly caused by the higher digestive availability and consequent hepatic oxidation of fatty acids. Significance: C. vulgaris, a microalga, is a novel feedstuff that is an alternative to conventional crops such as maize and soybean meal. Its recalcitrant cell wall may cause antinutritional effects when included in monogastric diets. This can be prevented by using exogenous enzyme supplementation, namely CAZymes, aimed at degrading this cell wall during digestion. Liver proteomics was used to identify the impact of these diets in finishing pig metabolism